Heating and cooling induced stresses and displacements in heat exchanger piles in sand. (March 2020) - Georgiadis, Konstantinos; Skordas, Dimitrios; Kamas, Ioannis; Comodromos, Emilios
Abstract: Heating and cooling of heat exchanger piles causes changes in the axial stresses in the pile and vertical pile displacements. Changes in axial stress (thermal stresses) are more significant in the case of fixed head piles, while vertical displacements are more important in the case of free head piles. This paper presents a series of finite element analyses that was performed in order to investigate the effect of the heating or cooling duration, the surface thermal boundary condition, the mechanical and thermal parameters of the soil and the temperature change in the pile, on the thermal stresses that develop in fixed head piles and the thermal vertical displacements of free head piles in sand. The numerical modelling procedure is first validated through the simulation of a set of published centrifuge experiments of heat exchanger model piles in sand. The results of an extensive parametric numerical investigation are then presented and the effect of the abovementioned potentially influencing factors is presented and discussed. Based on the numerical results, the most important parameters that affect the mechanical response of heat exchanger piles to heating or cooling are identified. Finally, design charts are proposed for the calculation of the maximum thermal stresses that develop in fixed head piles and the pile head thermal vertical displacement of free head piles.